Evaluating the Effectiveness of Augmented Reality in Mixed Reality Exhibition Spaces: A Multidisciplinary Perspective - Widjaja, Yunus; Junaidi, Junaidi; Solihatin, Etin (Bright Publisher, 2025)
In MR exhibition environments, the integration of AR provides a dynamic approach to increasing visitor engagement, encouraging interactive learning, and enhancing knowledge retention. However, the impact of AR on user experience and educational outcomes in these settings remains underexplored. This study investigates the role of AR in MR exhibitions, aiming to identify both its benefits and challenges. Using a mixed-methods research framework, this study combines qualitative and quantitative approaches to assess AR’s influence on visitor interaction and cognitive processing. Qualitative data is collected through ethnographic observations and structured user interviews, utilizing thematic analysis to identify engagement patterns and usability concerns. Quantitative data is gathered through eye-tracking metrics, user interaction logs, and pre- and post-exhibition knowledge assessments to measure cognitive load, retention rates, and engagement levels. Findings show that AR increases engagement by seamlessly integrating physical and digital elements to create immersive and intuitive experiences. Interactive storytelling and spatial learning mechanisms enhance knowledge retention. However, challenges such as technical limitations, accessibility barriers, and content development complexities restrict widespread adoption. This research contributes to the growing discourse on AR in cultural and educational contexts by offering evidence-based recommendations for optimizing its implementation. By focusing on user-centered design and interdisciplinary collaboration, the study identifies strategies for addressing challenges and maximizing AR’s potential in MR exhibitions. The findings are valuable for curators, designers, and educators seeking to create more effective and engaging exhibition experiences through AR.